MAKNA SIMBOLIK PRIA DAN WANITA DALAM TRADISI PERNIKAHAN - Sundari Eka Fitri (Jurnal Prodi Ilmu Komunikasi, 2023)
The study was intended to know the symbolic significance contained in the Metudau wedding procession of the abrahamic people of the ranau tribe of the south. The purpose of this study provides knowledge of how the symbolic meaning of men and women in the marriage procession of the Methuselah tradition and the construction of the meaning contained in the Metudau tradition. The study USES a qualitative approach using communication ethnographic analysis methods to obtain data and information in the way obervation, interviews, and documentation are necessary. Researchers employed the symbolic theory of interacism by George Herbert mead, which held the three concepts of mind, self, society, as defined in analyzing the significance of a symbol, acquired through social interaction, processed through the mind, reflected in oneself, and then engaged in society. The study of the tradition of Metudau/bujujokh established social and cultural norms according to the religious system and prevented the perversion of norms. The ancestors also wanted to form a characterised generation, because ranau people believed that children who were taught according to the customs and cultures in which they were born would create adab, norms and character.